Uma aplicação alternativa para agrupamento de galáxicas - Almirante, Adilson Oliveira de (2017)
In this work, we present an alternative method for clustering of galaxies, based on the data of galaxies available in large scale astronomical surveys. We have used the Friends of Friends (FoF) algorithm, as the basis of our clustering, with LL (Linking Length) and the minimum value of separation between galaxies, as our parameters. We have used a catalogue with approximately 44 thousand galaxies. After the simulation with six different values of LL, we analysed our clustering by means of the comparison with the obtained one by Tempel et al. (2016). In this comparison, we obtained a similarity of 79%. We also supplemented the validation of our method with an analysis of the silhouette coefficient, obtaining a general coefficient equal to 0.80. We present the characteristics of the groups obtained in our work, their comparison with the obtained one by Tempel et al. (2016) as well as the discussion with the non-grouped galaxies.